Docking field‐based QSAR and pharmacophore studies on the substituted pyrimidine derivatives targeting HIV‐1 reverse transcriptase. (18th September 2017) - Fan, Ningning; Zhang, Shuang; Sheng, Tao; Zhao, Liang; Liu, Zhenming; Liu, Junyi; Wang, Xiaowei
Abstract : HIV‐1 reverse transcriptase (RT) is one of the most important enzymes required for viral replication, thus acting as an attractive target for antiretroviral therapy. Pyrimidine analogues reportedly have selective inhibition on HIV‐1 RT with favorable antiviral activities in our previous study. To further explore the relationship between inhibitory activity and pharmacophoric characteristics, field‐based QSAR models were generated and validated using Schrodinger Suite (correlation coefficient of .8078, cross‐validated value of 0.5397 for training set and Q 2 of 0.4669, Pearson's r of .7357 for test set). Docking, pocket surfaces, and pharmacophore study were also investigated to define the binding pattern and pharmacophoric features, including (i) π–π interaction with residue Tyr181, Tyr188, and Trp229 and p–π interaction with His235 and (ii) hydrogen bond with residue Lys101 and halogen bond with residue Tyr188. The pharmacophore features of six‐point hypothesis AADRRR.184, AAADRR.38, and AADRRR.26 further complimented to the docking and QSAR results. We also found that the protein‐ligand complex exhibited high relative binding free energy. These observations could be potentially utilized to guide the rational design and optimization of novel HIV‐1 RT inhibitors. Abstract : The results of 3D‐QSAR, binding pocket, and pharmacophore analyses of pyrimidine HIV‐1 RT inhibitors would rationally clarify 3D‐QSAR and pharmacophore features of pyrimidine analogues and help in the design the potential inhibitors of HIV‐1 RT.